Revitalizing cultivation and strengthening the seed systems of fonio and Bambara groundnut in Mali through a community biodiversity management approach. Issue 2 (19th April 2020) - Sidibé, Amadou; Meldrum, Gennifer; Coulibaly, Harouna; Padulosi, Stefano; Traore, Issa; Diawara, Gaoussou; Sangaré, Adja Rokiatou; Mbosso, Charlie
Abstract: Fonio ( Digitaria exilis (Kippist) Stapf) and Bambara groundnut ( Vigna subterranea ( L. ) Verdc. ) are native crops grown at a small scale in Mali that have potential to support agricultural productivity under climate change. A community biodiversity management approach was explored in this study as a means to reinforce the cultivation of these crops by increasing farmers' access to intraspecific diversity and developing capacities of community institutions for their management. The research involved six communities in Ségou and Sikasso regions. Multiple varieties of fonio (10–12) and Bambara groundnut (8–12) were established in diversity fields in each site over 2 years where farmers engaged in experiential learning over the crop cycle. Significant adoption of fonio and Bambara groundnut was detected in several study sites. The precise drivers of adoption cannot be definitively determined but likely include increased seed access and awareness gained through the diversity field fora, seed fairs and community seed banks. No significant yield advantage was detected for any of the varieties in the diversity fields, which showed variable performance by site and year. The number of varieties registered and managed by community seed banks in each site increased from 1–5 varieties of each crop to 11–12 varieties following the interventions. The number of Bambara groundnut varieties cultivated in farmers' fields also increased, while there was evidence of a slight decline in fonio diversity in some communities. The results of this study can inform efforts to strengthen seed systems and cultivation of neglected and underutilized species in Africa.